2020
DOI: 10.1007/s11606-020-06353-5
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Clinical Risk Score to Predict 14-Day Occurrence of Hypoxia, ICU Admission, and Death Among Patients with Coronavirus Disease 2019

Abstract: Background Uncertainty surrounding COVID-19 regarding rapid progression to acute respiratory distress syndrome and unusual clinical characteristics make discharge from a monitored setting challenging. A clinical risk score to predict 14-day occurrence of hypoxia, ICU admission, and death is unavailable. Objective Derive and validate a risk score to predict suitability for discharge from a monitored setting among an early cohort of patients with COVID-19. Design Model derivation and validation in a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The scores discussed here all use no more than four variables that are relatively readily available in middle- to high-income countries. There also exists a simplified version of the CHOSEN score that does not rely on laboratory values but did also not perform as well in the original cohort [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scores discussed here all use no more than four variables that are relatively readily available in middle- to high-income countries. There also exists a simplified version of the CHOSEN score that does not rely on laboratory values but did also not perform as well in the original cohort [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression was defined as respiratory rate ≥ 30 breaths per minute (bpm), peripheral oxygen saturation (SpO 2 ) ≤ 93%, arterial partial oxygen pressure (PaO 2 )/fraction of inspired oxygen (FiO 2 ) ≤ 300 mmHg, mechanical ventilation or worsening of lung computer tomography (CT) findings [ 10 ]. The CHOSEN score used age, FiO 2 and albumin to predict progression defined as requiring supplemental oxygen, admission to the intensive care unit (ICU) or death [ 11 ]. The authors reported a good discriminative capacity for their score with an AUC of 0.89 (95%-CI 0.87–0.91) in their derivation and 0.87 (95%-CI 0.81–0.93) in their validation cohort [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other works presenting solutions from the MLDA domain can be consulted in Kirby et al [71], Joshi et al [69], and Van Klaveren et al [95] who performed a logistic regression model to identify variables associated with discharge appropriateness and optimization of healthcare ED resources during the pandemic. Other useful single-approached proposals can be found in Alfaro-Martinez et al [43], Freund et al [61], Brendish et al [49], Esposito et al [59], Gordon et al [66], Levine et al [74], Carlile et al [51], and García de Guadiana-Romualdo et al [63].…”
Section: Authors Technique Typementioning
confidence: 99%
“…Several biomarkers of clinical deterioration in COVID-19 have been identi ed, such as complete blood count (lymphocyte count (4) and neutrophil-to-lymphocyte ratio [NLR] (5)), biochemical tests (blood urea nitrogen [BUN] (6, 7) and lactate dehydrogenase [LDH] (8)), blood in ammatory markers (C-reactive protein [CRP], interleukin-6 [IL-6] (9, 10), and ferritin (11)), and blood coagulation tests (D-dimer (12)). Scoring models for risk strati cation have been developed using biomarkers, clinical signs, and imaging ndings (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, most reported prediction models are considered to have a high risk of bias and overestimation of their reported performance due to de cient temporal and external validation (29).…”
Section: Introductionmentioning
confidence: 99%